A novel framework of e-participation for smart cities - Yusuf, Muhammad; Alamsyah, Nurwahyu; Syarif, Muh.; Muntasa, Arif; Muzakki, Hakam (Association for Scientific Computing Electrical and Engineering, 2019)
The smart city is an exciting concept for improving the quality of the city. However, a smart city needs participation from citizens and all related stakeholders to use the technologies effectively in order to achieve the goal and solve the problems. Even though the city already has high-tech infrastructures, participation still required to provide ideas, inputs, and roles within the development of smart city concepts. This research aims to describe and analyze the current state of the e-Participation frameworks and propose a novel framework for smart cities. The analysis will go through a systematic literature review. Hopefully, this study makes contributions by providing a novel framework of e-Participation for smart cities. This research has implications for theory and practice. For theory, the novel framework can be added to the body of knowledge of e-participation, e-government, and smart cities fields. For practice, the framework will be useful for practitioners, policymakers, people and other stakeholders related to the smart city governance to increase citizen participation through technology-based services.